Development Of Lift The Flap Book Clean And Healthy Living Behaviour (PHBS) Material As Learning Medium For Slow Learner Student At SDN Pakal 1 Surabaya - Almira, Shafa (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Clean and Healthy Living Behavior (PHBS) implementation in elementary schools represents a concrete realization of national educational goals that should be universally applied, including to students with special needs such as slow learners. The lift the flap book serves as a tool to facilitate the learning process for slow learner students, specifically focusing on PHBS concepts within the school environment. This study aims to (1) explore the development process of the lift the flap book media containing PHBS material tailored for slow learner students at SDN Pakal 1 Surabaya, (2) assess the feasibility of the lift the flap book PHBS material for slow learner students at SDN Pakal 1 Surabaya, and (3) evaluate the effectiveness of the lift the flap book PHBS material for slow learner students at SDN Pakal 1 Surabaya. This research adopts a Research and Development approach utilizing the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation phases. The study sample comprised 10 slow learner students from SDN Pakal 1 Surabaya. Data collection involved Pre-Post Tests and attitude questionnaires, with analysis conducted using the Wilcoxon Test. Validation of the lift the flap book media from both content and media experts yielded an average score of 75%, indicating its feasibility. Moreover, statistical tests using the Wilcoxon Test revealed a significant positive impact of using the lift the flap book PHBS material on both the understanding and attitudes of slow learner students, with a significance level (Sig.) of 0.005 (<0.05).